Dever e universalismo moral em Hume: a normatividade sob uma perspectiva naturalista - Portela, Bruno Martinez (2017)
The present thesis aims to propose the rescue of the concepts of duty and of universalism in the perspective of a naturalistic ethics from the contemporary reading of the moral works of David Hume. It follows the hypothesis that there is textual basis in Hume for the defense of a moral theory with pretension to universality from the idea of a shared human nature and the role of reason, next to the sensibility, in our moral judgments. We have a common structure that allows us to communicate our feelings and moral judgments through a standard language, however, the naturalization of moral concepts through the sensitivity has as a burden of the recognition of a certain contingency usually associated with empiricism. However, we argue that this contingency should not be an impediment to normativity. In this sense, there are already elements in the Humean moral for the defense of a duty that arises from the mutual expectations that we have. These expectations are based on our feelings, but also depend on our ability to reflect. The general structure of the text will be as follows: we will present some considerations of modern morality by showing that Hume must be comprehended like a defender of a harmonious view of reason and sensibility. Next, we will present the natural and artificial virtues that are perceptions of the mind and it concerns the character traits of moral agents. In this sense, moral judgments refer not to actions, but to character. The third chapter presents an analysis of the debate about the is-ought problem that reappears with MacIntyre. The aim is to question the classical interpretation of this passage and to show that Humean morality is compatible with the idea of moral duties and that its criticism concerned modern intuitionist rationalism and religious morals. Without further impediments to the establishment of a notion of duty, we will seek in the next chapter textual basis for the universalistic aspects of Hume's morality, mainly considering the idea of a shared human nature and a language that reflects our sensitivity. In the final chapter, we will point out some contemporary moral theories that present an idea of normativity based on the notion of “common point of view”, whose idea of duty refers to the human point of view that is sensitive, reflective, and capable of improvement.